2009
DOI: 10.1038/cdd.2009.188
|View full text |Cite
|
Sign up to set email alerts
|

E2F1-inducible microRNA 449a/b suppresses cell proliferation and promotes apoptosis

Abstract: E2F1 is a positive regulator of cell cycle progression and also a potent inducer of apoptosis, especially when activated by DNA damage. We identified E2F1-inducible microRNAs (miRNAs) by microarray hybridization and found that the levels of miRNAs 449a and 449b, as well as their host gene CDC20B, are strongly upregulated by E2F1. High miR-449 levels were found in testes, lung, and trachea, but not in testicular and other cancer cells. MiR-449a/b structurally resemble the p53-inducible miRNA 34 family. In agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
165
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(183 citation statements)
references
References 40 publications
14
165
0
2
Order By: Relevance
“…Recently, a number of E2F-regulated miRNAs have been identified, including the miR-17-92, miR-106a-363, and miR-106b-25 clusters as well as miR-449a and miR-449b (18)(19)(20)(21)(22)(23)(24). In line with the complex nature of the RB/E2F pathway, some of these E2F-regulated miRNAs regulate E2Fs and/or other pathway components, thereby inhibiting E2F activity (18)(19)(20)22).…”
Section: Introductionmentioning
confidence: 92%
“…Recently, a number of E2F-regulated miRNAs have been identified, including the miR-17-92, miR-106a-363, and miR-106b-25 clusters as well as miR-449a and miR-449b (18)(19)(20)(21)(22)(23)(24). In line with the complex nature of the RB/E2F pathway, some of these E2F-regulated miRNAs regulate E2Fs and/or other pathway components, thereby inhibiting E2F activity (18)(19)(20)22).…”
Section: Introductionmentioning
confidence: 92%
“…It has been verified that miR-449 is down-regulated or lost in gastric cells, lung adenocarcinoma cell and testicular cancer cells [17][18][19][20] . In addition, our research demonstrates for the first time that in miRNA449b (rs10061133), G allele is significantly associated with an increased risk of susceptibility to HCC compared with A allele.…”
Section: Discussionmentioning
confidence: 99%
“…Some researches revealed that miR-3152 and miR-449 are involved in cancer [17][18][19][20] . MiR-3152 is up regulated in PDAC (pancreatic ductal adenocarcinoma), and miR-449 is down-regulated or lost in gastric cells, lung adenocarcinoma cells and testicular cancer cells.…”
mentioning
confidence: 99%
“…Significant progress in the understanding of E2F-mediated regulation of gene expression has been achieved by the finding that many microRNA-coding genes are bona fide E2F target genes (13)(14)(15)(16)(17)(18)(19)(20). In line with the complex nature of the E2F pathway, many reports have uncovered an essential role for E2F-regulated microRNAs in modulating distinct cellular processes, most notably pathways involved in neoplastic transformation (21,22).…”
Section: Introductionmentioning
confidence: 96%